Contextual Interference Effects on Approach Motivation When Learning Timing Tasks: A Frontal Electroencephalography (EEG) Alpha Asymmetry Study in Older Adults. Issue 4 (August 2022) - Beik, Meysam; Taheri, Hamidreza; Kakhki, Alireza Saberi; Ghoshuni, Majid; Fazeli, Davoud
In this study, we aimed to explore the effects of contextual interference on motivational regulation, as measured by EEG (frontal alpha asymmetry), in older adults. Participants practiced a sequenced timing task in random, algorithmic, or blocked schedules in both similar and dissimilar task difficulty conditions, with task difficulty defined by absolute timing goals (in ms) that were either close to each other (1350, 1500, 1650) or far from each other (1050, 1500, 1950), respectively. We assessed older participants' timing accuracy in these conditions, during acquisition and delayed retention learning, using the frontal alpha asymmetry index, recorded during practice, to measure motivation. On the accuracy measure in delayed retention, the algorithm practice schedule (in both similar and dissimilar conditions) was associated with significantly more accurate performance than random and blocked practice schedules. Also during delayed retention and in both task difficulty conditions, performance was better with a random schedule than a blocked schedule. On the EEG motivational measure, frontal alpha asymmetry was more often higher as practice progressed in the algorithm practice condition than in other practice conditions. However, in the random practice schedule, in late, versus early, acquisition, motivational regulation was higher. The blocked groups showed decreased motivation as practice progressed. We interpreted these findings to be in accordance with the challenge point framework and with OPTIMAL motor learning theory and valence hypothesis.